THE RELATIONSHIP OF CARIOGENIC FOOD CONSUMPTION WITH DENTAL CARARY IN CHILDREN (7-9 YEARS OLD) AT MARDIYUANA ELEMENTARY SCHOOL BOGOR : HUBUNGAN KONSUMSI MAKANAN KARIOGENIK DENGAN KEJADIAN KARIES GIGI PADA ANAK USIA SEKOLAH (7-9 TAHUN) DI SD MARDIYUANA KABUPATEN BOGOR - Al Muhajirin (Wijaya Husada, 2018)
Dental caries in children is a serious problem in oral health. In Indonesia prevalence of dental caries reached 90,05% in 2013. In Bogor prevalence of dental caries reached 60% in 2011. Primary of school age children are one group that is susceptible to get oral disease. Dental caries occur in children beacuse children like foods that are cariogenic which could mislead dental caries. The a ims of this study are determine the correlation cariogenic food consumption with behavior dental caries of school age children (7-9 year) in Mardiyuana Regency Bogor. This study used deskriptif analitik design and cross sectional approach. Technique sampling this study means with a total sampling with the number of respondents 98 people. Data collection was obtained througt a questionnaire. Statistic test shows that H0 was rejact and Ha acceped. Where the value is calculated by chi square test 0,000< 0,05 and using significancy level is 95%. The final conclution statustic test is a relationship between the consumption of cariogenic food with dental caries, so that, it can determine the correlation of cariogenic food with dental cariesof school age children (7-9year) in Mardiyuana regency Bogor.